A CRITIQUE BY DR. NABIL KUKALI ON AN ARTICLE ENTITLED: "The Case for an Israeli-Palestinian-Jordanian Confederation—Why Now and How?". (December 2022) - Kukali, Nabil
This essay offers a discussion and critique of Alon Ben-Meir's (2022) proposal entitled, "The Case for an Israeli-Palestinian-Jordanian Confederation: Why Now and How?" Incorporating elements of other viewpoints and prior proposals to add nuance, I explore Ben-Meir's concerted attempt to think past the exemplary two-state model for settling the Palestine and Israel conflict and to introduce thoughts on how policy makers and common actors can apply a confederal system later on. Given the entrenched one-state reality, I argue that the liberation of Palestinians through emancipation in a solitary popularity-based nation is the most thoughtfully clear option in contrast to many years of failed endeavors.